Improving the Ability to Understand Mathematical Concepts Through Problem-Based Learning (PBL) and Manipulatives in Class V Students of MIN 2 Pariaman City - Husna, Fitriatul (Journal of Development Education and Learning (JODEL), 2025)
Many primary school students struggle with conceptual understanding in mathematics, particularly in areas such as fractions, decimals, and measurement, which impedes problem-solving and transfer. This Classroom Action Research (PTK) investigates whether a Problem-Based Learning (PBL) model reinforced with manipulatives and a small project task can improve the conceptual understanding of Grade V students at MIN 2 Kota Pariaman. The research employed two cycles of action: planning, action, observation, and reflection. Participants were 18 Grade V students. Instruments included an 18-item concept test (pre-test and post-tests), observation checklists, project rubrics, work samples, and semi-structured interviews. Quantitative data were analyzed descriptively (means, percent meeting KKTP) and, where appropriate, paired comparisons; qualitative data were analyzed thematically. Mean scores improved from 61.40 (pre-test) to 74.10 (post-test I) and 86.00 (post-test II). The percentage of students meeting the established Kriteria Ketercapaian Tujuan Pembelajaran (KKTP) rose from 39% to 67% and then to 94%. Qualitative data indicated enhanced modelling, argumentation, collaboration, and motivation.